2020
DOI: 10.7717/peerj.8702
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock protein family geneHspa1lin male mice is dispensable for fertility

Abstract: Background Heat shock protein family A member 1 like (Hspa1l) is a member of the 70kD heat shock protein (Hsp70) family. HSPA1L is an ancient, evolutionarily conserved gene with a highly conserved domain structure. The gene is highly abundant and constitutively expressed in the mice testes. However, the role of Hspa1l in the testes has still not been elucidated. Methods Hspa1l-mutant mice were generated using the CRISPR/Cas9 system. Histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…In the present study, both of the two variants in WDR63 are located before the WD40 domain (p.Arg55* and p.Arg359*), leading to the loss of WD40 domains in WDR63 protein. The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both of the two variants in WDR63 are located before the WD40 domain (p.Arg55* and p.Arg359*), leading to the loss of WD40 domains in WDR63 protein. The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous report demonstrated that HSPA1L is mainly expressed in testis, and located in cytosol or nucleus 18 . Recently, Wang et al reported mRNA expressions of Hspa1l in mouse heart, liver, spleen, ling, kidney, brain, muscle, and testis 28 . We also detected the gene expression of Hspa1l in C57BL/6J mouse kidney tissues (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the binding of sperm to the zona pellucida GO term, we found several genes associated with spermatogenesis and fertilization, namely, HSPA1L (heat shock protein family A member 1 like), SPA17 (sperm autoantigenic protein 17), ZPBP (zona pellucida binding protein), and ZPBP2 (zona pellucida binding protein 2). HSPA1L has also been shown to be related to spermiogenesis in cattle, human, and mouse (Liu et al, 2019;Wang et al, 2020). This implies that DNA methylation patterns of key genes associated with spermatogenesis are highly conserved across species (Figure 3D, Supplementary Table S2).…”
Section: General Characteristics Of Sperm Dna Methylomementioning
confidence: 91%